2020
DOI: 10.1177/2319714520909006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Flipped Classroom Model: A Case Study from Oman

Abstract: The flipped learning approach over the years has gained importance, especially in higher educational establishments that primarily focus on more personalized learning for the students. In this context, the current study evaluates a flipped learning approach which was implemented by a higher education institution from the Middle East region as a pilot project and analyses the impact of the flipped approach on the student performance from the educators’ perspective. The study focuses on different aspects like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
3
5
0
3
Order By: Relevance
“…Table 1 revealed that 14 studies (66.65%) support the effectiveness of flipped learning in enhancing social science and humanities learning skills among students; 4 studies (19.5%) contributes to cognitive skills; 2 studies (9.50%) enhanced social skills; and 1 study (4.80%) contribute to personal skills of the students. The results supported the previous studies (He et al 2019;Jong, 2019;Maheshwari & Seth, 2018;Molnar, 2017;Pandow et al, 2020;Shih & Tsia, 2017;Talan & Gulsecen, 2019) who reported the effectiveness of flipped learning. These results can be linked to the importance of technology in higher education and in social science and humanities education, as well as consider as a preferred methods in the teaching and learning process.…”
Section: Findings and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Table 1 revealed that 14 studies (66.65%) support the effectiveness of flipped learning in enhancing social science and humanities learning skills among students; 4 studies (19.5%) contributes to cognitive skills; 2 studies (9.50%) enhanced social skills; and 1 study (4.80%) contribute to personal skills of the students. The results supported the previous studies (He et al 2019;Jong, 2019;Maheshwari & Seth, 2018;Molnar, 2017;Pandow et al, 2020;Shih & Tsia, 2017;Talan & Gulsecen, 2019) who reported the effectiveness of flipped learning. These results can be linked to the importance of technology in higher education and in social science and humanities education, as well as consider as a preferred methods in the teaching and learning process.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…The result also supported the claim that implementing flipped learning in the learning process could improve the learners' information and knowledge (Jong, 2019). These results may also be attributed to the learning procedures used in flipped learning that facilitate learning practices and understanding course materials (Nanclares & Rodríguez, 2016;Pandow et al, 2020), which helps them to gain various skills. Pandow et al, (2020) reported that flipped learning impacts students' knowledge, collaboration and problemsolving skills, helping them to take the responsibility of their learning and become selflearners.…”
Section: Findings and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Flipped classroom is a method where the teacher gives the content of a lesson in the form of videos to learners for them to watch at home and prepare before going to class [11]. Flipped classroom makes content of a lesson to be presented to learners online before the normal face-to-face lesson [12]. Studies revealed the identity of the one who presents the content in the video either on a disc or online.…”
Section: Introductionmentioning
confidence: 99%
“…In March 2020, we published an issue on 'Trust and Joy: Organizational Role of Thumb' with the objective to link and to find better ways to understand the boundary/ interface between organizational behaviour, organizational culture, organizational change; strategic implementations and strategic compatibility. Many interesting contributions (Bhattacharyya, 2020;Johnson, 2020;Ogbeibu et al, 2020;Pandow et al, 2020;Quttainah, 2020) added different flavours adding diversity, culture and organizational strategies to this issue. FIIB Business Review believes in hosting the most relevant and contemporary topics.…”
mentioning
confidence: 99%